High Levels of Residue within Polymeric Hollow Fiber Membranes Used for Blood Oxygenation. Issue 6 (November 2016) - Alexander, Joseph V.; Grulke, Eric A.; Zwischenberger, Joseph B.
Abstract : A number of research teams are developing surface coatings for hollow fiber membrane (HFM) blood oxygenators to improve their biocompatibility and service life. Surface coating techniques can be quite sensitive to the presence of contaminants on the exterior surface of the hollow fibers. We found large amounts of leachable oils associated with several commercial HFMs, i.e., as much as 2.5–7.5 weight percent. Leachable residues were suspected when a surface coating, a surface-initiated atom transfer radical polymerization (s-ATRP) of poly(ethylene glycol) methacrylate, resulted in areas of 100 µm 2 devoid of coatings on the exterior surfaces of HFMs. After leaching residual oils, s-ATRP coatings were uniform and continuous across the hollow fibers. Therefore, removal of residual material should be considered before applying coating technologies to commercial HFMs. The effects of such leachable agents on the performance of blood oxygenators are not known.